Analisis Penyebab Kerusakan Mesin Produksi Kayu Lapis - Bramantiyo Eko Putro; Moch Yusup A Aziz (Performa: Media Ilmiah Teknik Industri, 2020)
PT. Sama Al-Tanmiah is a company engaged in the semi-finished plywood production industry. Semi-finished raw materials are further processed according to the needs of the buyer, the cause of damage is due to poor maintenance and deteriorating component quality. This research was conducted to determine the origin of the causes of damage to the production machine at PT. Same Al-Tanmiah. Retrieval of data obtained by means of interviews, observation and requesting secondary data for 6 months of production, for data processing using Fault Tree Analysis and Failure Mode and Effect Analysis. The data obtained from the company enters into data management. The next stage will be a fault tree image analysis using Microsoft Visio and weighting to the three production machines using Microsoft Excel. The results of the researchers obtained the root of the fault tree and the value of the RPN with weighted machine damage. Improvement of management and standard operating procedures (SOP).